Biostratigraphy of the Early Turonian- Late Campanian pelagic limestone (Kometan and Gulneri formations) near Sayid Sadyq Town, Kurdistan Region, NE-Iraq. - Al-Khafaf, Araz Omer Salih (Sulaimani Journal for Pure and Applied Sciences, 2023)
This study aims at the presentation of a planktonic foraminiferal biozonation of the Late Cretaceous pelagic carbonate section in the east of the Sulaymaniyah governorate, Kurdistan region, Northeast of Iraq. The zonation proved the occurrence of the Kometan and Gulneri formations which belong to the Early Turonian – Late Campanian age. This is achieved by taking fifty-two (52) samples from the lower part of the section to the upper one with an interval of two meters between successive samples. From these samples, sixty-two (62) thin sections are prepared and (43) species from (11) genera of planktonic foraminifera are indicated and identified in the two formations of the studied section. According to the First and Last occurrence of identified planktonic foraminiferal assemblage, the studied section is divided into seven biozones, from older to young. These biozones are Whitenella archaeocretacea Heterohelix moremani Total Range Zone, Marginotruncana sigali Partial Range Zone, Dicarinella concavata Interval Range Zone, Dicarinella asymetrica Total Range Zone, Globotruncanita elevata Partial Range Zone, Globotruncana ventricosa Interval Range Zone, Radotruncana calcarata Total Range Zone. The age of the two Formations is assigned as Early Turonian- Late Campanian based on the planktonic foraminiferal ranges from the lower part of the section to the upper part. The boundary of the Gulneri and Balambo formations is gradation while there is a gap between the former formation and Kometan Formation
Keywords: Planktonic foraminifera; Early Turonian; Late Campanian; Cretaceous Biozonation; Sulaymaniyah Governorate; Kurdistan Region; Northeast Iraq